Shear-flow characteristics of rock fractures and implications for injection-induced seismicity - Ji, Yinlin (Nanyang Technological University, 2020)
Harvesting heat trapped in geothermal reservoirs has the potential to offer an affordable and sustainable solution for reducing the current dependence on fossil fuels. Hydraulic stimulation has been employed to enhance the permeability of geothermal reservoirs and to maintain the productivity of renewable heat. However, the effectiveness of heat extraction depends not only on the permeability of fractured granite but also on the injection-driven instability of pre-existing and hydraulically induced fractures. Over the past decades, induced seismicity resulted from fluid injection has sparked huge concerns for the safety and efficiency of deep geothermal systems. Therefore, understanding the mechanisms of injection-driven fracture instability is critical to the optimization of hydraulic stimulation strategies.